Diversity, species coexistence and functional composition patterns in subtropical Atlantic Forests invaded by non-native trees - Larsen J.G.* (2024)
© 2023 The Authors. Functional Ecology © 2023 British Ecological Society.Biological invasions are a major environmental challenge today. Interactions between invasive and native species can significantly shape community structures, influencing coexistence, diversity and functional composition of species. The subtropical Atlantic Forest in southern Brazil, a recognized biodiversity hotspot, provides a unique setting to study these interactions, given its vulnerability to alien tree invasions. Our study sought to elucidate the impacts of such invasions on this fragile ecosystem by addressing key questions: (1) How are tree community diversity patterns affected by the abundance of invading alien tree species? (2) What are the patterns of coexistence between native and alien invasive trees? (3) Is the functional composition of the forests altered by the abundance of invasive trees? To address these questions, we compiled data on the abundance and functional traits of native and invasive trees. We determined the diversity patterns and functional composition of plots with different degrees of invasion. These data were analysed using generalized linear mixed models, principal component analysis and a coexistence index. In plots with a higher abundance of invasive trees, there was a significant decrease in the taxonomic and functional richness (FRic) of native species. Furthermore, we observed that invasive alien trees coexisted with native species, and as the abundance of invasive trees increased, the native community-weighted mean of the leaf area (LA) and specific leaf area (SLA) decreased. In conclusion, within the subtropical Atlantic Forest areas of southern Brazil, our findings highlight that the abundance of invasive trees adversely affects the taxonomic and FRic of native species. Furthermore, while invasive alien trees were found to coexist with native species, increased invasive abundance corresponded to a reduction in the LA and the SLA of the native community. Read the free Plain Language Summary for this article on the Journal blog.